(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The status of History education within a Social Science education framework of the Lesotho educational system is a cause for concern. In an attempt to foster the development goals of the Kingdom of Lesotho, education and especially Social Science education were identified as a major role player. In spite of this realisation, History education, and to a lesser extent Geography education was identified as liabilities that could be substituted with other disciplines such as Development Studies. Geography had, however, gradually regained a position as a major Social Science discipline while History education is still considered unimportant in relation to national needs. The evidence is that many schools in Lesotho do not offer History as a subject and both students and teachers of history are not taken seriously as academics. Against this backdrop, this article explores the situation from historical and pedagogic perspectives. I draw considerable examples from contexts such as Cameroon and South Africa, where I have had the opportunity to experience the fragile nature and status of History education both as student and teacher/lecturer. I then suggest why any consideration of Social Sciences with the exclusion of History education will not lead to the desired national goals, thereby justifying the need for a turnaround strategy that favours the teaching and learning of History in Lesotho. The article concludes with recommendations and the prospects for the future, based on the issues raised and discussed.